Subject-verb agreement inflection in Arabic-speaking individuals with Down syndrome. - Mashaqba, Bassil; Al Khalaf, Eman; Huneety, Anas; Abu Sa'aleek, Haneen (Clinical Linguistics & Phonetics, 2024)
This research examines the production of subject-verb agreement inflection in person, number, and gender in Urban Jordanian Arabic-speaking individuals with Down syndrome (DS). Third person singular masculine, third person singular feminine, and third person plural suffixes (3MS/3FS/3P) were investigated to achieve this objective. The research involved 60 participants, 30 males and 30 females, enrolled in Nazik Al Hariri Welfare Center for Special Education in Amman. The participants were divided into three groups by age, kindergarten 2 (7.1 to 12.5), school-age (13.10 to 17.6), and vocational training (18.3 to 27.3). Data were collected via a picture-naming task. The results showed that verb agreement constitutes a severe problem in individuals with DS. All three age groups showed some degree of language decline. The 3MS form was the most used and the most accurate form by the three DS groups (48.5%), followed by the 3FS (35.3%) and the 3P (22.8%). A significant finding of this study is that the acquisition of agreement for person, number, and gender by the DS groups is associated with inconsistency and atypical asynchrony. In addition, the results show that age significantly affects the DS groups' production of subject-verb agreement. Thus, the study recommends early intervention for the verb system and subject-verb agreement.